Non-English Majored Students‟ Perceptions and Practice of Self-Assessment in Writing English Paragraphs: A Study at a College in the Mekong Delta : - Nguyễn, Thị Thanh Quyên (Trường đại học Cần Thơ, 2018)
The current study aims to answer two questions including: What are non-English majored students‟ perceptions of self-assessment in writing English paragraphs? How do the students practice self-assessment in writing English paragraphs?